Responding to protracted displacement using the Humanitarian-Development-Peace nexus approach: UNDP and UNHCR theory of change - Rebecca Roberts (United Nations Research Institute for Social Development (UNRISD), 2020)
The increasingly complex and protracted nature of forced displacement has precipitated a renewed interest in adopting a Humanitarian-Development-Peace (HDP) nexus approach in the UN, the international community and among donors. The project developed a Theory of Change (ToC) for use at the country level to support UNDP-UNHCR collaboration on forced protracted displacement; to understand how UNDP-UNHCR intervention responses support forcibly displaced persons, host populations and host governments; and to inform measures to prevent displacement. Responses should be people centred, needs based and not status based, so UNDP and UNHCR should work with other organizations to support different displaced groups depending on mandate, capacity and the presence of stakeholders. Contexts vary so target populations might, for example, include refugees and asylum seekers, internally displaced persons (IDPs), returnees and stateless persons alongside host populations.
Keywords: 330